The Relationship Between Job Satisfaction and Organizational Commitment on Turnover Intentions Among Zoo Negara Malaysia Staff - Nazafar, Idris (2011)
The main objective of this study is to examine whether there is any relationship between job satisfaction, organizational commitment and turnover intentions among employees of ZNM. The study also determines the level of turnover intentions. The study hypothesized that job satisfaction and organizational commitment were having negative relationship with turnover intentions. The methods used in the research to obtain data were via questionnaire. A total of ninety (90) employees of ZNM were selected by modified systematic sampling as the sample of study. The tests involved were Factor Analysis, Descriptive Statistics and Multiple Regression. This study found that job satisfaction has a negative relationship to turnover intentions. The non significance relationship found between organizational commitment and turnover intentions.